Relationship between Attitude and Preventive Behavior of Increased Uric Acid Levels in the Elderly - Endang Yuswatiningsih; Agustina Maunaturrohmah (Babali Nursing Research, 2022)
Introduction: The increase in the number and life expectancy of the elderly causes problems and various needs of the elderly. Increasing age makes physiological functions decrease due to degenerative processes (aging). One of the diseases experienced by the elderly is gout. The purpose of this study was to analyze the relationship between attitudes and behavior to prevent increased uric acid levels in the elderly. Methods: The design of this research is analytic with a cross-sectional approach. The population in this study were all the elderly in Ngudirejo Village, Diwek District, Jombang Regency as many as 120 elderly and the number of samples was 92 respondents using a simple random sampling technique. Collecting data using a questionnaire about attitudes and behavior to prevent an increase in uric acid. Data processing by editing, coding, scoring, tabulating, and analysis using the Spearman Rank Correlation statistical test with an alpha of 0.05. Results: The results showed that the attitudes of the elderly were positive as many as 62 respondents (67%) and negative as many as 30 respondents (33%), while for the prevention behavior of increasing uric acid levels both 29 respondents (32%), enough were 42 respondents (46%) and less as many as 21 respondents (22%). The results of the analysis test showed that the value of p = 0.000 was smaller than the alpha value of 0.05 so the alternative hypothesis was accepted. Conclusion: The conclusion in this study is that there is a relationship between attitudes and behavior to prevent an increase in uric acid levels in the elderly. The results of this study imply the importance of attitudes and behavior in preventing an increase in uric acid levels in the elderly.